Usefulness of Alcohol Septal Ablation in the Left Ventricular Outflow Tract Obstruction in Fabry Disease Cardiomyopathy - Zemánek, David; Marek, Josef; Dostálová, Gabriela; Magage, Sudheera; Roblová, Lenka; Kovárník, Tomáš; Linhart, Aleš (The American journal of cardiology, 2021)
Fabry disease (FD) is an X-linked linked genetic disorder caused by α-galactosidase A deficiency. The typical clinical manifestation is left ventricular hypertrophy, often mimicking hypertrophic cardiomyopathy (HC). In contrast to sarcomeric HC, left ventricular outflow tract obstruction (LVOTO) is less frequent. We describe 6 male patients with genetically confirmed FD and symptomatic LVOTO. All of them underwent a transcatheter alcohol septal ablation with an immediate effect on the obstruction in all cases and without any serious complications. The median LVOT maximal pressure gradient was 85 (60 to 170) mm Hg. The hemodynamic effect persisted during subsequent follow-up (ranging from 6 months to 16 years). Five patients reported substantial symptomatic improvement. Four patients were receiving specific FD therapy before the interventional procedure. In conclusion, alcohol septal ablation appears to be effective in the treatment of LVOTO in patients with FD and appears to be comparable to the limited published experience with surgical septal myectomy. Despite some important differences between FD HC and sarcomeric HC, the recommendation for treating LVOTO should be similar.
Keywords: echokardiografie; dospělí; ethanol; Adult; lidé; Ablation Techniques; Fabryho nemoc; Echocardiography; Ventricular Outflow Obstruction; Electrocardiography; Ethanol; elektrokardiografie; Male; Fabry Disease; lidé středního věku; mužské pohlaví; obstrukce výtoku ze srdeční komory; ablace; Middle Aged; Humans